The importance of implementing reporting according to esg requirements and linking it to iso standards - Novakova, Renata; Skýpalová, Renata; Pauliková, Alena; Plaksiuk, Olena; Плаксюк, Олена Олександрівна (Запоріжжя : ТДАТУ, 2025)
Currently, entire company managements are being retrained in the field of reporting based on EU requirements related to ESG (Environment, Social, Government). On November 10, 2022, the European Parliament approved the CSRD1 directive on corporate sustainability reporting, which replaces the current NFRD2 directive. The CSRD introduces new obligations in non-financial reporting for a wider range of companies. The new CSRD directive entered into force on January 5, 2023 and is expected to affect approximately 50,000 companies across the European Union.
Keywords: environmental information; social information; corporate governance